2020
DOI: 10.1111/bcpt.13452
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant effects of 3‐(3,4‐methylenedioxy‐5‐trifluoromethyl phenyl)‐2E‐propenoic acid isobutyl amide involve TSPO‐mediated mitophagy signalling pathway

Abstract: Piper laetispicum C. DC is one of the Chinese herbal medicines used for alleviating depressive disorders. G11-5 [3-(3, 4-methylenedioxy-5-trifluoromethyl phenyl)-2Epropenoic acid isobutyl amide] is synthesized based on the chemical structure of an active integrant of Piper laetispicum C. DC. The present study assessed the antidepressant effect of G11-5 and investigated the underlying mechanism with learned helplessness (LH) and social defeat stress (SDS) mice model of depression. In the LH model, mice were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…DC., exhibited a significant antidepressant effect through the TSPO-mediated mitophagy pathway. 28 Therefore, these studies clearly demonstrate that Piper laetispicum C. Dc. and its extract may have antidepressant effects.…”
Section: Discussionmentioning
confidence: 57%
“…DC., exhibited a significant antidepressant effect through the TSPO-mediated mitophagy pathway. 28 Therefore, these studies clearly demonstrate that Piper laetispicum C. Dc. and its extract may have antidepressant effects.…”
Section: Discussionmentioning
confidence: 57%
“…Studies have revealed inhibited mitophagy levels in animal models of depression induced by learned helplessness (LH) and social defeat stress (SDS). These models showed substantial decreases in the expression of key proteins involved in mitophagy such as TSPO, Parkin, VDAC1, and the autophagy initiator protein Beclin-1 (Li et al, 2016;Wei et al, 2020). Similarly, mitophagy suppression was observed in the hippocampus of rats induced with chronic CUMS.…”
Section: Impaired Mitophagy In Mdd Modelsmentioning
confidence: 90%
“…G11-5 can improve depression-like behavior in LH and SDS mice, and leads to an increased success rate for electric shock escape and greater total distance traveled during OFT movement, as well as reduced FST immobility time. Furthermore, G11-5 regulated mitophagy levels and increasing the expression of TSPO, Parkin, VDAC1, and autophagy promoter Beclin-1 in the brain of LH mice (Wei et al, 2020). Microglia are the resident immune surveillance cells of the central nervous system (von Bernhardi et al, 2016).…”
Section: The Effect Of Chinese Herbal Medicine On Mitophagymentioning
confidence: 99%
“…Several studies have reported that mitophagy and subsequent mitochondrial dysfunction are significant contributors to the pathophysiology of MDD [ 9 11 ]. Mitophagy has also been considered the emerging mechanism of action for some antidepressants [ 12 , 13 ]. Shu et al discovered that the antidepressant fluoxetine protects astrocytes by enhancing astrocytic mitophagy and removing damaged mitochondria in a corticosteroid-treated cell model [ 12 ].…”
Section: Introductionmentioning
confidence: 99%